The Rhapsody of mobile application : a case study of Malaysia travellers - Osman, Sharina; Mohd. Din, Shamzani Affendy (Springer, 2022)
The growing speed of technology has profoundly transformed tourism industry and challenged the value proposition of many tourism businesses. Tourism, as a service industry, has been particularly impacted by technological disruptions that have entirely changed how people travel. The development in technology is aimed to benefit the tourism industry, and mobile technologies have tremendously changed tourists’ experiences as well as the distribution channel of tourism products. Mobile applications exist for tourists to access information virtually at any time and from any place where they can make travelling plans and arrangement including accommodation reservation, flight trackers, food ordering, destination guides, online travel agencies, attraction guides, and payment. Comparing several studies on various mobile technology applications, this chapter provides insight on the adoption of these applications from tourists’ perspective. It explores the different types of mobile applications available and how tourists use them.